General relativity and the Einstein equations - Choquet-Bruhat, Yvonne (Oxford : Oxford University Press, 2009)
Aimed at researchers in mathematics and physics, this monograph in which the author overviews the basic ideas in general relativity, introduces the necessary mathematics and discusses some of the key open questions in the field.
Description based on print version record.
Includes bibliographical references and index.
Keywords: General relativity (Physics) -- Mathematics